Konstruksi Hukum Pembuktian Penuntut Umum Terhadap Sonny Widjaja Dalam Kasus Korupsi PT. ASABRI - Fadila, Jihan; Alfitra, Alfitra (JOURNAL of LEGAL RESEARCH, 2024)
Evidence is crucial to the criminal process, especially in corruption cases. This study analyzes the strength of the evidence presented by the Public Prosecutor in the corruption case of the reconstruction of investment funds of PT. ASABRI with Sonny Widjaja's response. The focus of this study is to assess the extent to which the evidence meets the elements of a crime as regulated in Article 2, paragraph (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption. This study uses a normative method with a statutory regulatory approach and a case approach. The study results indicate that the Public Prosecutor proved the elements unlawful, enriching oneself or others and causing losses to state finances with a loss value of Rp22.78 trillion. The evidence was carried out through five main pieces of evidence, namely witness statements, expert statements, letters, statements from prostitutes, and clues, including electronic evidence. The Panel of Judges accepted the evidence and declared the perpetrator guilty based on the primary charge, thus imposing a prison sentence of 18 years and a fine of Rp750 million. This study confirms that a strong evidentiary strategy by the Public Prosecutor plays an essential role in shaping the judge's conviction and upholding justice in large-scale corruption cases.